The impact of audit committee characteristics on corporate voluntary disclosure - Madi, Hisham Kamel; Ishak, Zuaini; Abdul Manaf, Nor Aziah (Elsevier Ltd., 2014)
The purpose of this study is to investigate the influence of audit committee characteristics on corporate voluntary disclosure of 146 Malaysian listed firms for the year 2009.Based on content analysis of disclosure, the empirical results of multiple regressions reveal that audit committee independence, size and multiple directorships of audit committee members are positively associated with corporate voluntary disclosure.Frequency of meetings and financial expertise of audit committee members are not significantly associated with corporate voluntary disclosure.The results offer evidence to policy makers, investors and accounting professionals on the extent to which audit committee characteristics associated with such committee effectiveness in monitoring corporate reporting processes.